47.4k views
0 votes
Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!

Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz Help!Plz-example-1
User Pubudu
by
4.9k points

2 Answers

3 votes

Answer:

4

Explanation:

4 Is the Answer because you have to multiply 4 to all the N's. Which means you have to multiply 4 by 3 which equals 12. Then 2+4=6. Then you would do 12-6=6. There's your answer. Here is the equation if it were like the problem: 12 - (2+4). I'm sure you can figure out the rest. Thanks. If you find any fault in my answer let me know! Have a good day!

User Phils
by
5.2k points
5 votes

Answer: n=4

Explanation:

Given

3n-(2+n)=6

Expand Parenthesis (REMEMBER TO CHANGE SIGNS)

3n-2-n=6

Combine like terms

2n-2=6

Add 2 on both sides

2n-2+2=6+2

2n=8

Divide both sides by 2

2n/2=8/2

n=4

Hope this helps!! :)

Please let me know if you have any questions

User Ilya Karpeev
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.